2007
DOI: 10.1002/tox.20264
|View full text |Cite
|
Sign up to set email alerts
|

Subacute toxicity evaluation in rats exposed to concrete and hwangto building environments

Abstract: This study examined the potential adverse effects of the subacute exposure of rats to concrete and hwangto building environments. Polycarbonate was used as a comparison. Groups of 10 male rats were exposed to polycarbonate, concrete, or hwangto cages for a 4-week period in summer or winter. During the study period, the clinical signs, mortality, skin temperature, body weight, food consumption, ophthalmoscopy, urinalysis, hematology, serum biochemistry, gross findings, organ weights, and histopathology were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 28 publications
4
14
3
Order By: Relevance
“…Therefore, it was concluded that the lower skin temperature induced by exposure to the low-temperature environment was the main cause of the adverse effects observed in the concrete group. In this study, the mean temperature (11.9-12.51C) of the internal air in the rat housing systems during the study period was similar to the results (11.7-12.11C) of a previous study (Lee et al, 2007). In addition, there was a higher incidence and severity of clinical signs in the concrete group than in the hwangto group, which is also consistent with a previous subacute toxicity study (Lee et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Therefore, it was concluded that the lower skin temperature induced by exposure to the low-temperature environment was the main cause of the adverse effects observed in the concrete group. In this study, the mean temperature (11.9-12.51C) of the internal air in the rat housing systems during the study period was similar to the results (11.7-12.11C) of a previous study (Lee et al, 2007). In addition, there was a higher incidence and severity of clinical signs in the concrete group than in the hwangto group, which is also consistent with a previous subacute toxicity study (Lee et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…The incidence and severity of these clinical signs were somewhat higher in the concrete group than in the control and hwangto groups. These findings are uncommon in normal Sprague-Dawley rats (Kim et al, 2004(Kim et al, , 2006 but are consistent with the results of a previous subacute toxicity study (Lee et al, 2007). According to the subacute toxicity study, 4-week continuous exposure to concrete building environments under cool temperatures had significant adverse effects on the clinical signs, skin temperature, body weight, food intake, organ weight, and histopathology in rats.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations